Grammar Skills of Secondary Teacher Education Students in a State University: Basis for Worktext Development - Sahagun, Reyna Lyn A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
The study aimed to determine the standing in the grammar of the freshmen secondary teacher education students of a state university in Zambales, Philippines. Using descriptive research, a questionnaire served as the main instrument in gathering data involving eighty (80) students. A typical respondent is between 16-18 years old, female, speaks Filipino at home, prefers to read in English, and loves short stories as a genre to read. The grammar test consists of three parts: speech; subject-verb agreement; and phrases, clauses, sentences, and sentence patterns. The respondents got the highest scores in the parts of speech. There was a significant increase in their post-test scores. The students should explore and study English grammar and should give more time to appreciate it fully. Gender, language spoken at home, preferred reading materials, and genres should not affect the students' learning. A regular encouragement might help them enhance the students’ grammar skills. Students should practice using English at home, explore reading other genres to develop effective reading habits. The teachers should develop more exciting and up-to-date teaching strategies on improving the students' grammar skills. A worktext can be developed based on the results of the study.